Indikator - Indikator yang Memengaruhi Produktivitas Kerja Karyawan pada Suatu Perusahaan - Aang Syahdina; Sarah Nurjanah; Warjudin Warjudin; Jordan Ismadi; Yulia Novarini; Khofifah Nurul (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is intended to determine the impact of incentives, work discipline, and work performance at PT Kreasi Produk Nusantara. The study involved 65 people. The research this time was quantitative, and the questions consisted of a list that used Slovin for measurement. SEM-PLS software version 3.0 was used to analyze the research data and process it. The results revealed that incentives have a significant effect on employee productivity, while work discipline and work performance have no significant effect on employee productivity.